Dari Gang Sempit ke Sentra UMKM: Inovasi Corporate Social Responsibility dalam Pemberdayaan Masyarakat Urban - Rina Ekawati; Dadan Abdan Sakur; Ari Djanuar Prasetyo (Jurnal Transformasi Bisnis Digital, 2025)
Urban space limitations and community economic empowerment needs present complex challenges in Corporate Social Responsibility (CSR) implementation in densely populated areas. This study aims to analyze the effectiveness of MSME empowerment programs through optimizing narrow alleys into productive economic centers in Duren Tiga Village, South Jakarta. Using mixed methods research with sequential explanatory design and CIPP evaluation model, the study involved 9 assisted MSMEs, PT PLN Puslitbang management, and related stakeholders during August 2024-July 2025 period. Results show that transformation of 200 m² narrow alley into Café Mini Forest successfully increased average MSME turnover by 67.9% and halal certification achievement by 88.9%. The program integrates "go global, go digital, go green" approach with multi-stakeholder partnership model contributing to SDGs 1, 8, 12, and 17. Spatial optimization innovation creates economic multiplier effects through 250% foot traffic increase and cost-efficient shared facilities. This model proves that community empowerment-based CSR can transform limited spaces into sustainable economic ecosystems, offering a replicable framework for similar urban empowerment programs.